ACADEMIC PROCRASTINATION, TEST ANXIETY AND SELF-ESTEEM AS CORRELATES OF SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT IN CHEMISTRY IN ANAMBRA STATE, NIGERIA (UNIZIK Journal of STM Education, 2023)
This study determined academic procrastination, test anxiety and self-esteem as correlate of secondary school students’ academic achievement in chemistry. Four research questions guided the study and four null hypotheses were formulated and tested. A correlational research design was adopted for the study. This study was carried out in Anambra State. The population of the study consisted of all the 8,081 Senior Secondary School II (SS2) Chemistry students in the 263 public secondary schools in the six education zones in Anambra State. The sample size consisted of 1,500 SS2 chemistry students. Multistage sampling technique was used in selecting the sample size. Data for this study was collected by means of structuredquestionnaire. The first instrument is titled Tuckman Procrastination Scale, TPS (adapted) which was originally developed by B. W. Tuckman. The second instrument is titled Test Anxiety Scale, TAS (adapted) which was developed by Sarason (1980). The third instrument is titled Rosenberg’s Self-esteem Scale, RSES. The fourth instrument is an achievement test measured using the cumulative/average score of SS 2 students’ internal (termly) examination scores. The instruments were subjected to face and content validation by three experts. TPS and TAS were subjected to test of internal consistency using Cronbach Alpha method and reliability values of 0.87 and 0.81 respectively were obtained. In answering the research questions, Pearson Product Moment was used while t-test of correlational analysis was used to test the null hypotheses at 0.05 alpha level. It was found out that there is a strong positive relationship among academic procrastination, test anxiety, self-esteem and academic achievement scores of secondary school students in Chemistry. Based on the findings, it was recommended amongst others that teachers and school administration should enlighten students to practice how to manage their time as precisely as possible to reduce the anxiety associated with rushing to meet up with deadlines at the last minute due to purposeful delays in carrying out academic tasks.
Keywords: Academic Procrastination; Test Anxiety; Self Esteem; Academic Achievement; Chemistry